Zarządzanie placówką oświatową – pomiędzy ideałami a rzeczywistością - Roman Pawłowski, Roman Pawłowski; Wołoszyn, Beata (Studia Edukacyjne, 2020)
The aim of this article is to present dilemmas that are experienced by directors/headmasters of educational institutions. On the one hand, they carry out tasks strictly defined by the education law documents, on the other hand, they are expected to create educational leadership. Reality shows that, what the directors would like the most is to pursue directing an education institution in the democratic style, but just as often, in fact, they represent an authoritarian management style. This stems from the multiplicity of tasks they have to perform and the external pressure of the governing authority, the pedagogical supervisory body and the influence of state policy. This situation raises concerns about the functioning of educational institutions and the final outcome of formal education: effective education for life in a democratic society.